2010
DOI: 10.1016/j.virol.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Gr-1+ cells, but not neutrophils, limit virus replication and lesion development following flank infection of mice with herpes simplex virus type-1

Abstract: Neutrophils are prominent in epidermal and dermal layers of human herpetic lesions and are rapidly recruited into the skin follow epidermal abrasion and infection of mice with herpes simplex virus type-1 (HSV-1). Herein, we demonstrate that early production of neutrophil-attracting chemokines KC/MIP-2 is associated with transient recruitment of neutrophils into the skin of HSV-1-infected mice in temporal association with the development of herpetic lesions. Treatment of HSV-1-infected mice with a Ly6G-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 72 publications
8
36
0
Order By: Relevance
“…Our study targeted Ly6G specifically using a different antibody (clone 1A8) that does not recognize significant populations of activated T or B lymphocytes (55). Gr-1-expressing cells, but not Ly6G ϩ cells, have previously been implicated in protection against herpes simplex virus 1 (HSV-1) infection (56,57), indicating a clear difference in the antiviral roles of these different populations of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our study targeted Ly6G specifically using a different antibody (clone 1A8) that does not recognize significant populations of activated T or B lymphocytes (55). Gr-1-expressing cells, but not Ly6G ϩ cells, have previously been implicated in protection against herpes simplex virus 1 (HSV-1) infection (56,57), indicating a clear difference in the antiviral roles of these different populations of cells.…”
Section: Discussionmentioning
confidence: 99%
“…In an HSV-1 skin flank infection model, mice depleted of GR1 + cells had increased viral loads and lesion severity. This effect was not observed in mice depleted of Ly6G + cells (including neutrophils and G-MDSCs) (164), suggesting that Ly6C…”
Section: Direct Targeting Of Mdscs In Vivomentioning
confidence: 93%
“…During HSV-1 and HSV-2 infection of mice, cells phenotypically resembling MDSCs infiltrated the cornea (34) and skin (40,164). In one study, increased herpes simplex keratitis (HSK) and viral titers were observed in HSV-1-infected Kit W-sh mice (that lack CD31 + mast cells), compared to wildtype mice (130).…”
Section: Dna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…These cell types share effector mechanisms, and both are recruited to sites of infection, but they differ in their mechanisms of activation and recruitment; recently, they have been shown to make differential contributions to the control of Listeria monocytogenes and herpes simplex virus 1 (33,34). The antibody depletion of Gr-1 ϩ cells is unable to distinguish the contribution of each cell type given the affinity of RB6-8C5 for Ly-6C and Ly-6G, with Ly-6G being found selectively on neutrophils and Ly-6C being No antibody C57BL/6 Background *** *** found on neutrophils, subsets of CCR2 ϩ inflammatory monocytes, myeloid suppressor cells, and memory subsets of CD8 ϩ T cells (35,36).…”
Section: Discussionmentioning
confidence: 99%